2012
DOI: 10.1371/journal.pone.0052180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grazing Intensity and Environmental Factors on Species Composition and Diversity in Typical Steppe of Inner Mongolia, China

Abstract: In the present study, we aim to analyze the effect of grazing, precipitation and temperature on plant species dynamics in the typical steppe of Inner Mongolia, P.R. China. By uncoupling biotic and abiotic factors, we provide essential information on the main drivers determining species composition and species diversity. Effects of grazing by sheep were studied in a controlled experiment along a gradient of seven grazing intensities (from ungrazed to very heavily grazed) during six consecutive years (2005–2010)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 51 publications
8
63
0
2
Order By: Relevance
“…These finding suggest that moderately grazed swamp plant communities lose vegetation but still retain their overall structure in responses to moderate grazing intensity. Our study supports the intermediate disturbance hypothesis (Connell, 1978) as we found negative diversity effects of low and high grazing intensity on the swamp plant communities (Ren et al, 2012). Notably, moderate grazing intensity showed significant differences in community composition when compared to high and low grazing intensity according to the examined PCA axis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These finding suggest that moderately grazed swamp plant communities lose vegetation but still retain their overall structure in responses to moderate grazing intensity. Our study supports the intermediate disturbance hypothesis (Connell, 1978) as we found negative diversity effects of low and high grazing intensity on the swamp plant communities (Ren et al, 2012). Notably, moderate grazing intensity showed significant differences in community composition when compared to high and low grazing intensity according to the examined PCA axis.…”
Section: Discussionsupporting
confidence: 90%
“…In this study we demonstrated how different grazing intensities influence species richness and composition, suggesting grazing functions as either a neutral or negative feedback for swamp plant community composition. http Previous studies of grazing intensity on the diversity of wetland and grassland ecosystems have been mixed in their findings with some reporting a positive and some a negative diversity response to intense grazing (Bullock et al, 2001;Cingolani et al, 2005;Grace et al, 2007;Ren et al, 2012). In general, however, many studies suggest that high grazing pressure likely reduces biodiversity, potentially influencing keystone species, and that biodiversity conservation benefits through reducing high level grazing to a medium grazing intensity (Jones, 2000;Davies et al, 2010 that grazing intensity significantly influence the local species composition (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the simplicity, by assuming that grazing and climate independently (but not interactively) influenced grass production, this study computed grass removal rate as difference of natural NPP less actual NPP. Although previous field experiments (e.g., [50][51][52]) found that the grass production in a dry year was mainly controlled by precipitation and temperature while the grass production in a wet year was primarily affected by grazing, [53] postulated that grazing and climate can somewhat interactively influence grass production and that such an interactive influence can either be positive or negative, depending on a number of not-easy-to-be-quantified factors (e.g., grazing intensity and pattern). Thus, our simple method may overestimate the grass removal rate for one year, while it can underestimate the grass removal rate for another year.…”
Section: Analysis Of Grazing Removal Ratementioning
confidence: 99%
“…Animal grazing is the most dominant land use of grasslands (Mavromihalis et al 2013). Grazing influence on the relative abundance of C 4 plants has received much attention in the study of grasslands in North and South America (Reeder et al 2004;Altesor et al 2006;Derner et al 2006), Central Asia (Auerswald et al 2012;Ren et al 2012), South Africa (Franz-Odendaal et al 2002), Australia (Bell et al 2012) and New Zealand (Crush and Rowarth 2007). Most of these studies suggest that grazing increases the relative abundance of C 4 species in some plant communities (Reeder et al 2004;Waters et al 2005;Fanselow et al 2011).…”
Section: Introductionmentioning
confidence: 99%